2021
DOI: 10.1101/2021.07.18.452807
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Artificial Intelligence-rationalized balanced PPARα/γ dual agonism resets the dysregulated macrophage processes in inflammatory bowel disease

Abstract: A computational platform, the Boolean network explorer (BoNE), has recently been developed to infuse AI-enhanced precision into drug discovery; it enables querying and navigating invariant Boolean Implication Networks of disease maps for prioritizing high-value targets. Here we used BoNE to query an Inflammatory Bowel Disease (IBD)-map and prioritize a therapeutic strategy that involves dual agonism of two nuclear receptors, PPARα/γ. Balanced agonism of PPARα/γ was predicted to modulate macrophage processes, a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…We asked if the protective actions of MDP require GIV. Compared to WT controls, the GIV-KO mice developed significantly worse DSS-induced acute colitis ( Fig 3A ), as determined by histological composite scores accounting for deformation of colon crypts and increased immune infiltration in the colon ( Fig 3B-C ) and disease activity index ( Fig 3D-E ); the latter is a composite score of stool consistency, weight loss and the presence of fecal blood (Katkar et al 2021; Swanson et al 2020; Whittem et al 2010) . Pre-treatment with MDP ameliorated the severity of colitis in WT, but not GIV-KO mice ( Fig 3B-E ).…”
Section: Resultsmentioning
confidence: 99%
“…We asked if the protective actions of MDP require GIV. Compared to WT controls, the GIV-KO mice developed significantly worse DSS-induced acute colitis ( Fig 3A ), as determined by histological composite scores accounting for deformation of colon crypts and increased immune infiltration in the colon ( Fig 3B-C ) and disease activity index ( Fig 3D-E ); the latter is a composite score of stool consistency, weight loss and the presence of fecal blood (Katkar et al 2021; Swanson et al 2020; Whittem et al 2010) . Pre-treatment with MDP ameliorated the severity of colitis in WT, but not GIV-KO mice ( Fig 3B-E ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the pan-JAK-inhibitor Tofacitinib has succeeded in Phase III trials for UC, with conflicting results in CD 76 , and our findings suggest that targeted trials on the S2FCD molecular subtype using JAK1/2-selective inhibitors (e.g., Upadacitinib, Filgotinib or Baricitinib) may have demonstrable efficacy. As for IDICD, the strategy of improving microbial clearance using the balanced dual-PPARα/γ agonism with PAR5359 was identified using an AI-guided network transcriptomics approach 20,72 , which is predicted to protect the gut mucosal barrier in IBD and represents a new class of therapy in IBD yet to enter clinical trials.…”
Section: Molecular Classification That Informs the Choice Of Therapeu...mentioning
confidence: 99%
“…These findings agree with the prior findings of downregulated transcripts of multiple cytokines (Figure 2D-bottom left) and confirm the presence of an immune suppressed state in the setting of infection. We asked if impaired bacterial clearance in CD-EDMs can be reversed by a balanced dual agonist of PPARα/γ, PAR5359 71 , which has recently been shown to accelerate bacterial clearance in CD-patient derived PBMCs and ameliorate colitis in both DSS-induced chemical and Citrobacter-induced infectious colitis models 72 . We found that treatment of the CD-EDMs with PAR5359 significantly reduced the bacterial burden (Figure 5I-right), with virtually no effect on healthy-EDMs (Figure 5I-left).…”
Section: S2fcd and Idicd Show Subtype-defining Phenomes That Are Ther...mentioning
confidence: 99%
“…We have demonstrated the dueling relationship between PPARγ and PPARα in terms of macrophage differentiation, bacterial and viral clearance, IBD, and atherosclerosis. A PPARγ/α dual agonist seems to be more promising in terms of therapeutics and activation of both receptors would counter the each other’s side effects while still providing better pharmacological effects ( 184 ). Another notable example is how PPARγ agonists have been used as a therapeutic drug for increasing insulin resistance in diabetic patients as well as lipid metabolism in patients with atherosclerosis.…”
Section: The Future Of Ppar In Therapeuticsmentioning
confidence: 99%